28 Remote transmissions from injectable implantable loop recorders – an increasing healthcare burden. (16th October 2019) - Nolan, P; Nash, P; Smyth, Y; McNeill, B; Crowley, J
Abstract : Background: Implantable Loop Recorders (ILRs) provide long term ECG monitoring for patients for a number of presentations. It has a Class I indication for investigation of recurrent syncope (ESC 2018 Syncope Guidelines) and a Class IIa indication for documenting silent atrial fibrillation in patients with a cryptogenic stroke (ESC 2016 Atrial Fibrillation Guidelines). The miniaturisation of ILRs and their "injectable" nature has increased their clinical use. The addition of remote monitoring with alert notification allows for early detection of significant events in these patients, however false activation of automatic detection algorithms results in inappropriate remote transmissions and unnecessary use of Cardiac Physiologist time. Aim: The aim of the study was to look at the true and false activation rates from patients implanted with ILRs from a specific manufacturer, the number of those activations, and to classify the reason for those activations. Methods: The transmissions from patients implanted with ILRs from a single manufacturer between Aug 2017 and Jun 2018 were analysed retrospectively. All transmissions from the date of implant to Jul 2019 were analysed. Where there was any doubt about the nature of a detection an opinion of a Cardiologist was sought. Data around indication for implant, the number and nature of true and false activations were recorded. For false activations, the reasons for these were also noted. Results: 41 ILRs were implanted in this period in 21 males and 20 females. Ages at time of implant ranges from 17.93–79.78 yrs (avg 49.41 yrs). 80% were implanted for investigation of syncope, 7% for palpitations, 5% for AF detection and 7% for other indications. The total number of monitoring days across the total patient population was 3185 days with the average monitoring period being 77.68 (range 10–224) days. 23 pts (56.1%) made a total of 93 patient activated events. Only two patients' recordings showed significant findings, an SVT and a broad complex tachycardia. 6 pts' (14.6%) ILRs automatically detected a total of 37 true arrhythmias, 26 AF, 1 pause and 10 SVT events 26 pts' (63.4%) ILRs automatically detected a total of 46, 604 false arrhythmia detections. This equated to 14.63 false transmissions per day of monitoring. The types and reasons for false activations are shown in table 1. Conclusion: In this analysis of episodes sent by ILRs on remote monitoring 91.8% of episodes were due to false triggering of automatic device detection. In 96.8% of these cases this was due to undersensing of the QRS complex by the ILR. This analysis highlights the significant burden of remote follow-up of ILRs, particularly that of false triggering of automatic device detection algorithms. It also highlights that over 96% of false triggering are due to undersensing, highlighting the importance of achieving good amplitude QRS signals at implant.